A CRITICAL REVIEW OF PURPOSE OF DOSAGE OF SNEHA IN UTTAMA MATRA SUGGESTED BY CHARAKA - Chandaliya Sachin Shantilal; Chandaliya Deepali Sachin; Kaloge Smita Vinayak; Daware Pournima Macchindra (International Journal of Applied Ayurved Research, 2015)
Intake of Sneha (unctuous) articles before Vamana and Virechana is mandatory preprocedure. The dosage of Sneha is managed in such a way that it shall reach to every cell of the body to loosen the bonds of humours with that of channels. It is a widely accepted assumption that Charaka had advocated the dose of sneha in a Madhyama matra (quantity of sneha which will get digested in twelve hours) while Vagbhata suggested it in an Uttama Matra (highest quantity of sneha which will get digested in twenty four hours). But after critical analysis of texts it is found that Charaka actually advocated both Uttama and Madhyama Matra for Shodhana (purificatory procedures which expel humours from the body) while Vagbhata suggested only Uttama Matra. In the present article the basis for this theory is hypothecated and proven in “Panchavayava method in (five steps to prove a principle)” method.